Analisis Kinerja Keuangan Bank Umum Syariah Melalui Pendekatan Islamicity Performance Index - Safaah Restuning Hayati; Mutiah Hanifah Ramadhani (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine how the financial performance of Islamic commercial banks in Indonesia through the islamicity performance index approach for the period 2013-2017, by the principles of justice, halalness, and purification. This study using quantitative descriptive research. The number of banks sampled are five Islamic commercial banks in Indonesia that have been selected, through a purposive sampling technique first. These banks are BRI Syariah, BNI Syariah, Mandiri Syariah, BCA Syariah, and Victoria Syariah. The type of data used is secondary data taken from the financial statements of each islamic commercial bank that is sampled. Through the islamicity performance index approach, the results of this study indicate that the financial performance of islamic commercial bank is unsatisfactory, based on the average of the variables that have been processed in accordance with predicate valuation standards.